Investigating the indoor environment quality parameters on occupants’ satisfaction and well-being: a review - Esfandiari, Masoud; Suzaini Mohamed Zaid,; Muhammad Azzam Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Occupants’ comfort is a critical area of research which has a lot of aspects; however, when it comes to building the indoor environment quality is a highlighted fact with a strong influence on occupants’ comfort and well-being. In this regard, this study tried to go through the science world and document the parameters of the indoor environment quality which has a massive effect on occupants’ comfort and well-being. Following parameters have shaped the body of knowledge for this study as a thermal comfort, indoor air quality, lighting quality, acoustic quality. The importance of these parameters is not only because of their critical influence but they have a complex relationship with each other as well as their relationship with energy saving and their effect on occupants’ productivity. According to the finding of post occupancy researchers, the designers and any one whose has a role in building construction should consider the effect of IEQ on occupants’ comfort at the very first stage of the design while it should be considered in the life cycle of the building as well to provide satisfaction for occupants. Therefore, this paper has brought the effort to investigate how the IEQ parameters affect occupants and document the information for those who want to understand IEQ relationship with occupants’ comfort, well-being and health.